2017
DOI: 10.1002/jsfa.8687
|View full text |Cite
|
Sign up to set email alerts
|

Rare sugars, d‐allulose, d‐tagatose and d‐sorbose, differently modulate lipid metabolism in rats

Abstract: BACKGROUND: Rare sugars including D-allulose, D-tagatose, and D-sorbose are present in limited quantities in nature; some of these rare sugars are now commercially produced using microbial enzymes. Apart from the anti-obesity and anti-hyperglycaemic activities of D-allulose, effects of these sugars on lipid metabolism have not been investigated. Therefore, we aimed to determine if and how D-tagatose and D-sorbose modulate lipid metabolism in rats. After feeding these rare sugars to rats, parameters on lipid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
(50 reference statements)
0
28
0
Order By: Relevance
“…A study in rats found that D‐allulose and D‐sorbose lowered hepatic lipogenic enzyme activity, whereas D‐tagatose increased its enzymatic activity (Nagata et al., 2018), which is of particular importance as increased lipogenesis is associated with metabolic syndrome (Sato et al., 2010). Serum adiponectin, a protein involved in glucose signaling and fatty acid breakdown, was lower in all rats on diets containing rare sugars (either D‐allulose, D‐sorbose, or D‐tagatose); however, only D‐sorbose showed a significant difference.…”
Section: Metabolism Of Sweetenersmentioning
confidence: 99%
“…A study in rats found that D‐allulose and D‐sorbose lowered hepatic lipogenic enzyme activity, whereas D‐tagatose increased its enzymatic activity (Nagata et al., 2018), which is of particular importance as increased lipogenesis is associated with metabolic syndrome (Sato et al., 2010). Serum adiponectin, a protein involved in glucose signaling and fatty acid breakdown, was lower in all rats on diets containing rare sugars (either D‐allulose, D‐sorbose, or D‐tagatose); however, only D‐sorbose showed a significant difference.…”
Section: Metabolism Of Sweetenersmentioning
confidence: 99%
“…Meanwhile, galactose has been commonly used to induce senescence in vitro and in vivo ( Azman and Zakaria, 2019 ). Intriguingly, sorbitose has not been reported as a component of other oligosaccharides, but has been reported to decrease lipid metabolism in rats ( Nagata et al, 2018 ). Thus, sorbitose may account for the characteristic activity of PNO.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the observed changes in enzyme activity were accompanied by reductions in adipose tissue weight (41; 48; 71; 73) , although in two shorter studies the reductions did not reach significance (65; 68) . Interestingly when Nagata et al (68) compared the effects of 3% PSI, TAG and SOR in the diets of rats, they found that lipid metabolism enzymes were affected differently by the different rare sugars, for example the activity of fatty acid synthase was decreased in PSI-fed rats but increased in the TAG-fed group.…”
Section: Rare Sugar Consumption and Lipid Metabolismmentioning
confidence: 99%